Cognitive-behavioural group treatment for a range of functional somatic syndromes: randomised trial. - Schröder, A; Rehfeld, E; Ornbøl, E; Sharpe, M; Licht, R; Fink, P (2012)
BACKGROUND: Many specialty-specific functional somatic syndrome diagnoses exist to describe people who are experiencing so-called medically unexplained symptoms. Although cognitive-behavioural therapy can be effective in the management of such syndromes, it is rarely available. A cognitive-behavioural therapy suitable for group treatment of people with different functional somatic syndromes could address this problem. AIMS: To test the efficacy of a cognitive-behavioural therapy (Specialised Treatment for Severe Bodily Distress Syndromes, STreSS) designed for patients with a range of severe functional somatic syndromes. METHOD: A randomised controlled trial (clinicaltrials.gov, NCT00132197) compared STreSS (nine 3.5 h sessions over 4 months, n = 54) with enhanced usual care (management by primary care physician or medical specialist, n = 66). The primary outcome was improvement in aggregate score on subscales of the 36-item Short Form Health Survey (physical functioning, bodily pain and vitality) at 16 months. RESULTS: Participants receiving STreSS had a greater improvement on the primary outcome (adjusted mean difference 4.0, 95% CI 1.4-6.6, P = 0.002) and on most secondary outcomes. CONCLUSIONS: In the management of functional somatic syndromes, a cognitive-behavioural group treatment was more effective than enhanced usual care.